2021
DOI: 10.1002/mrd.23457
|View full text |Cite
|
Sign up to set email alerts
|

miR‐221‐3p regulates apoptosis of ovarian granulosa cells via targeting FOXO1 in older women with diminished ovarian reserve (DOR)

Abstract: In our earlier study, we showed that the expression of microRNA‐221‐3p (miR‐221‐3p) was significantly lower in women of advanced age with diminished ovarian reserve (DOR) compared with young women with normal ovarian reserve (NOR). Therefore, in this study, we aimed to explore how miR‐221‐3p regulates apoptosis of granulosa cells and the pathogenesis of DOR. Bioinformatics prediction and dual‐luciferase reporter assay were conducted to identify the target gene of miR‐221‐3p. miR‐221‐3p expression was manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…miR-221 regulates a target, Dickkopf 2, subsequently inhibiting the activation of the Wnt/β-catenin pathways (Chen et al 2020 ). An inverse relationship between miR-221 and FOXO1 (downregulation of miR-221/upregulation of FOXO1) has been reported in ovarian cells in menopause (Wei et al 2021 ). Overexpression of miR-221 can directly increase the growth and proliferation of PDAC cells by downregulating PTEN expression and upregulating phospho-Akt expression (Yang et al 2016 ).…”
Section: Discussionmentioning
confidence: 94%
“…miR-221 regulates a target, Dickkopf 2, subsequently inhibiting the activation of the Wnt/β-catenin pathways (Chen et al 2020 ). An inverse relationship between miR-221 and FOXO1 (downregulation of miR-221/upregulation of FOXO1) has been reported in ovarian cells in menopause (Wei et al 2021 ). Overexpression of miR-221 can directly increase the growth and proliferation of PDAC cells by downregulating PTEN expression and upregulating phospho-Akt expression (Yang et al 2016 ).…”
Section: Discussionmentioning
confidence: 94%
“…Our experimental results revealed that high-dose administration of RD inhibited the damage caused by CTX in ovarian reserve and granulosa cells. Of note, as a major cause of DOR, the apoptosis of ovarian granulosa cells has been a consistent research focus concerning the etiology of DOR [ 33 ]. FOXO1 expression was found to be downregulated in granulosa cells from patients with poor ovarian reserve [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non-coding RNAs, 20–25 nucleotides in length. Considering the critical role of miRNAs in regulating gene expression and interactive signaling events ( Flynt and Lai, 2008 ), their involvement in cumulus and granulosa cells has been demonstrated ( Chen et al, 2017 ; Hong et al, 2018 ; Kim et al, 2021a ; Wei et al, 2021 ). Despite the widespread application of miRNA sequencing ( Raza et al, 2022 ), the effect of acupuncture on miRNA profiling in DOR rats has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%